Fancy Nancy, poison ivy expert - O'Connor, Jane (I can read! Beginning reading 1, 2009)
A young girl who uses fancy words and considers herself practically a poison ivy expert learns a valuable (and itchy) lesson about the plant after picking a bouquet of wildflowers.